Estabilidad y cambio del voto por la derecha en Chile a la luz de las elecciones presidenciales del 2009 - López V., Miguel Ángel; Dockendorff V., Andrés; Figueroa R., Pedro L. (Revista de Sociología, 2011)
The analysis of the election results in Chile which put an end to the Concertation governments and the arrival to power of the center-right Coalition for Change shows the absence of a general realignment of the Chilean voter. This is relevant not only to explain Sebastian Piñera’s victory but also to understand the dynamic of electoral stability and change in the post-transitional Chilean democracy. From the analysis of the electoral results obtained at the coalition level, the present article demonstrates that one of the main characteristics of the electoral process in the recovered democracy has been the stability of the Chilean voter; although the 2009-2010 elections represented the end of 20 years of predominance of the center-left coalition and alternance in power, from a theoretical point of view they are “normal” and not “critical elections”, following Converse and V.O. Key’s nomenclature. Finally, conclusions show that it is not possible to talk of an electoral split or cataclysm, neither of major readjustments of the power relationships in the Chilean political system, as it is reflected by the Congress composition.